A new sport from Sweden (Fiep Bulletin - online, 2015)
Swedes are probably the most sports-minded people in the world today. One out of every four persons of an entire population of seven millions is a subscribing and active member of some officially recognized sports or atheletic club. Six out of 50 and one out of every ten women between the ages of 15 and 40 take part regularly in some organized game or sport. Many more engage in out-of-doors activities which it is impossible to enumerate